An in vitro study on the most effective concentration and contact time of honey solution against streptococcus mutans - Dones, Dan Frederick D.
Honey has already been proven by various studies to be particularly beneficial in promoting oral wellness through its antibacterial property. Recent in-vitro studies have concluded that honey has inhibitory effects against Streptococcus mutans. However, there is no study yet that proved what exact amount of honey dilution is needed to maximize its antimicrobial potential. The objective of this study is to determine the most effective concentration and contact time to honey solution against S. mutans. Two phases of experimentation were done. The first phase focused on determining the most effective concentration of honey solution that can best inhibit the growth of S. mutans. Five (5) concentrations of honey solutions: 75%, 80%, 85%, 90% and 95% and control (distilled water) were prepared and subjected to disk diffusion test. The diameter of the zone of inhibition, as exhibited by the clear zone surrounding the filter paper disc was measured and recorded. The second phase focused on determining the most effective contact time while using the most effective concentration from phase one. Contact times tested were 15, 30, 45 and 60 seconds where the growth of the test organisms were observed and recorded as either present (+) or absent (-) Phase one results showed that the largest diameter of clear zone was found in 90% honey with 16.53mm mean diameter of clear zone. An increasing trend of mean diameter of clear zones was noted as the concentration of honey increases: 0 mm for 0% 2.73 mm for 75% 12.13 mm for 80% and 13.07 mm for 85%. But, a slight decrease of diameter was noted on 95% with 16.20 mm. One-way ANOVA test revealed that there is a significant difference among the means of the zones of inhibition at p-value = 0.05. Phase two showed inconsistencies on the gathered data where in some of the plates which showed absence of growth at a lower contact times, unexpectedly showed presence of growth after some time. Chi-square test revealed that there is no difference on inhibition of growth of S. mutans at different contact times at p- value = 0.05. Based on the results of the study, its can be concluded that the most effective concentration of honey solution in inhibiting the growth of S. mutans is 90%. However, there is no significant difference among 80%, 85%, 90% and 95% of honey solution. In addition, all the contract times tested in this study was found to be not statistically different from each other.